Diversity of phosphate solubilizing bacteria and fungi from andisol soil affected by the eruption of Mount Sinabung, North Sumatra, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Sembiring M, Sabrina T. 2021. Diversity of phosphate solubilizing bacteria and fungi from andisol soil affected by the eruption of Mount Sinabung, North Sumatra, Indonesia. Biodiversitas 23: 713-719. Phosphate solubilizing microbes are present in all locations with different population levels. The eruption of Mount Sinabung in 2013 resulted in changes in soil pH and the soil’s microbial population, such as phosphate solubilizing microbes. This research aimed to obtain environmentally-specific phosphate solubilizing microbes derived from andisol soil impacted by the eruption of Mount Sinabung, which excelled in increasing the availability of phosphate. Sampling was conducted in Desa Kutarayat, Naman Teran Sub-district, Karo District, North Sumatra Province, Indonesia. Isolation of phosphate solubilizing microbes was carried out on pikovskaya media, and test of phosphate solubilizing microbes potential was conducted on solid and liquid pikovskaya media. Organic acid content was determined using high performance liquid chromatography (HPLC) and microbial identification was performed using PCR-sequencing. The result showed that 4 isolates of each phosphate-soluble fungi and bacteria were isolated from andisol soil affected by the eruption of Sinabung mountain. It was also observed that phosphate solubilizing microbes’ ability to produce organic acids varied. The obtained fungi could dissolve P in some phosphate source either on solid media or liquid medium. Talaromyces pinophilus (J2) can increase the highest availability of P in andisol soil.
Keywords: Andisol, phosphate solubilizing fungi, pikovskaya media, P available, Talaromyces pinophilus